2003
DOI: 10.1016/s0736-0266(03)00062-7
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapeutic agents sensitize sarcoma cell lines to tumor necrosis factor‐related apoptosis‐inducing ligand‐induced caspase‐8 activation, apoptosis and loss of mitochondrial membrane potential

Abstract: Chemotherapeutic agents have been used for the treatment of patients with Osteosarcoma (0s). However, inherent or acquired resistance to these agents is a serious problem in the management of 0 s patients. Tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) is considered to induce apoptosis in a variety of cancer cells but not normal cells. In the present study, we examined whether chemotherapeutic agents enhance TRAIL-induced apoptosis in the sarcoma cell lines MG-63 and SaOS-2. Pretreatment with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 37 publications
2
24
0
Order By: Relevance
“…4,5 Therefore, new treatment modalities for sarcoma are urgently required. We have recently found that CDDP or DXR induces apoptosis in sarcoma cell lines MG-63 and SaOS-2, 21 as reported in other cell types. 30,31 However, molecular mechanisms of the apoptotic cell death induced by DNA-damaging agents are not completely known.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…4,5 Therefore, new treatment modalities for sarcoma are urgently required. We have recently found that CDDP or DXR induces apoptosis in sarcoma cell lines MG-63 and SaOS-2, 21 as reported in other cell types. 30,31 However, molecular mechanisms of the apoptotic cell death induced by DNA-damaging agents are not completely known.…”
Section: Discussionsupporting
confidence: 79%
“…After exposure to 3 mg/mL CDDP or 3 mg/mL DXR for 24 h, the percentage of apoptotic cell death was determined using an Annexin V-Cy5 Apoptosis Detection Kit (BioVision, Inc., Mountain View, CA), as previously described, 21 which detects redistribution of intracellular phosphatidylserine on the extracellular surface. Briefly, cells (1 Â 10 5 /0.5 mL binding buffer) were incubated with 5 mL Cy5 conjugated Annexin V protein for 5 min, followed by flow cytometric analysis using a Nippon Becton Dickinson FACSCalibur cytometer (Tokyo, Japan).…”
Section: Flow Cytometric Analysis Of Apoptotic Cellsmentioning
confidence: 99%
“…Synergistic interactions have been reported between TRAIL and a number of therapeutic agents, including IFN-alpha 35) , genotoxic agents such as doxorubicin, cisplatin, or etoposide [36][37][38][39][40][41] , irinotecan 24,29,34,[42][43][44] , gamma-radiation 45,46) , and cyclooxygenase-2 inhibitors 47) . Although the mechanisms of these synergies are not completely understood and are likely to vary between therapies, the following mechanisms have been suggested to influence the combination treatments synergies detected to date: receptor up-regulation, modulation of Bcl-2 family members, up-regulation of caspases, down-regulation of c-FLIP, which is an endogenous inhibitor of "extrinsic" caspase-8 activation, and inhibition of IAP family members, which inhibit "intrinsic" caspase-3 activation.…”
Section: Therapeutic Approaches Using Trailmentioning
confidence: 99%
“…TRAIL exhibits selective cytotoxicity towards cancer cells; and recombinant TRAIL and agonistic TRAIL-R1/R2 monoclonal antibodies are being developed as novel anti-cancer agents for a variety of malignancies [5]. However, many osteosarcomas are resistant to TRAIL, and induction of apoptosis requires combination treatment with other chemotherapeutic agents [6,7]. …”
Section: Introductionmentioning
confidence: 99%